M3+[amaranth red]3− (M = La, Gd): a novel sulfonate-based inorganic–organic hybrid nanomaterial for multimodal imaging. Issue 16 (28th April 2015) - Poß, Marieke; Napp, Joanna; Niehaus, Oliver; Pöttgen, Rainer; Alves, Frauke; Feldmann, Claus
<x xml:space="preserve">Abstract</x> [M3+][AMA]3− hybrid nanoparticles consist of M3+ (M = La, Gd) and the fluorescent dye anion [AMA]3− (AMA: amaranth red) and show multimodal functionality (fluorescence, magnetism) at excellent photostability.